Contribution of Burkholderia cenocepacia Flagella to Infectivity and Inflammation - Urban, Teresa A. (American Society for Microbiology, 2004)
Burkholderia cenocepacia is an opportunistic pathogen that can cause severe lung infections in cystic fibrosis patients. To understand the contribution of B. cenocepacia flagella to infection, a strain mutated in the major flagellin subunit, fliCII, was constructed in B. cenocepacia K56-2 and tested in a murine agar bead model of lung infection. C57/BL6 mice infected with ∼10(8) wild-type K56-2 bacteria exhibited 40% mortality after 3 days, whereas no mortality was noted in mice infected with the fliCII mutant. Among the mice surviving the infection with either strain, there was no significant difference in the bacterial loads in the lungs and spleen, bacteremia, weight loss, or infiltration of immune effector cells at 3 days postinfection. Similar results were observed at 24 h, prior to expression of the lethality phenotype. KC, a murine interleukin-8 (IL-8) homolog, was elevated in both the bronchoalveolar lavage fluid and serum of mice infected with the wild type compared to the fliCII mutant at 24 h, suggesting that flagella stimulated host cells. To demonstrate that flagella contributed to these responses, the interaction between B. cenocepacia and Toll-like receptor 5 (TLR5) was investigated. Infection of HEK293 cells with heat-killed wild-type K56-2, but not infection with the fliCII mutant, resulted in both NF-κB activation and IL-8 secretion that was dependent upon expression of TLR5. Together, these results demonstrate that B. cenocepacia flagella contribute to virulence in an in vivo infection model, and that induction of host immune responses through interaction with TLR5 may contribute to its overall pathogenic potential.